2020
DOI: 10.1155/2020/8209727
|View full text |Cite
|
Sign up to set email alerts
|

Local and Systemic Oxidative Stress in Balkan Endemic Nephropathy Is Not Associated with Xanthine Oxidase Activity

Abstract: Balkan endemic nephropathy (BEN) represents a chronic tubulointerstitial nephropathy which is followed by the progression of kidney fibrosis to end-stage kidney failure. The critical involvement of poisons in food (aristolochic acid (AA), ochratoxin, and heavy metals) and selenium deficiency are among nutritive factors which contribute to the pathogenesis of BEN, due to reactive oxygen species (ROS) liberation and/or decreased antioxidative defence system. The aim of the study is to distinguish a possible syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…OS, fibrosis, and inflammation are thought to play a role in the development and progression of BEN, but existing data are limited. Veljkovic et al performed a cross-sectional study including 50 patients diagnosed with BEN and 38 healthy controls and found that, compared to controls, BEN patients exhibited significantly increased systemic lipid and protein oxidation status, assessed by plasma thiobarbituric acid reactive substances (TBARS) and advanced oxidation protein products (AOPPs), respectively [ 10 ]. However, in urine, only AOPP levels were significantly higher compared to controls; the urine local lipid oxidation state was not different among groups, probably due to the reduced urine lipid content.…”
mentioning
confidence: 99%
“…OS, fibrosis, and inflammation are thought to play a role in the development and progression of BEN, but existing data are limited. Veljkovic et al performed a cross-sectional study including 50 patients diagnosed with BEN and 38 healthy controls and found that, compared to controls, BEN patients exhibited significantly increased systemic lipid and protein oxidation status, assessed by plasma thiobarbituric acid reactive substances (TBARS) and advanced oxidation protein products (AOPPs), respectively [ 10 ]. However, in urine, only AOPP levels were significantly higher compared to controls; the urine local lipid oxidation state was not different among groups, probably due to the reduced urine lipid content.…”
mentioning
confidence: 99%